Thinking feminist and gender studies now : Roundtable with the Centre for Gender Studies at the University of Stavanger - Myong, Lene; Engebretsen, Elisabeth Lund; Klitgård, Mathias; Hellstrand, Ingvil (Septentrio Conference Series, 2019)
The field of gender studies is changing and solidifying at the same time. What kinds of developments can we trace in contemporary gender studies, and what is at stake for gender studies now? What are important questions for/in the field? How come gender studies in Norway (and the rest of Scandinavia) tend to shoulder or “house” adjacent fields that also deal with questions of power and difference, such as critical race studies for example? Why are we working in/with gender studies, and how do we contribute towards advancing gender and feminist studies in theory, teaching, politics and practice? In this roundtable, scholars in the Centre for Gender Studies at the University of Stavanger grapple with these questions through examples from our own research and teaching. The purpose for this roundtable is to continue our local discussions and thinking with the field of gender studies nationally and internationally.